2022
DOI: 10.1002/eat.23668
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity is associated with eating disorders independent of depression and anxiety: Findings from the 2020–2021 Healthy Minds Study

Abstract: Objective To examine the association between food insecurity and eating disorder (ED) risk independent of co‐occurring anxiety/depression. Method Data were provided by 121,627 undergraduate/graduate students who participated in the 2020–2021 Healthy Minds Study (HMS). Participants responded to questionnaire measures of food insecurity and risk for EDs, depression, and anxiety. Established cut‐offs were used to identify students with food insecurity and probable psychopathology. Separate modified Poisson regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Food insecurity (i.e., concern about, or actual changes in, food availability) has been associated with binge eating and binge eating disorder (BED), bulimia nervosa (BN), as well as general ED pathology and symptomatology (Becker et al, 2017 ; Hazzard et al, 2020 ; Lydecker & Grilo, 2019 ; Rasmusson et al, 2019 ; Zickgraf et al, 2022 ). Food insecurity may be exacerbated during COVID‐19 due to increased financial stress and economic limitations, as well as the “panic buying” behaviors and shortage of staple foods that characterized the initial phases of the pandemic (Khosravi, 2020 ; Weissman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity (i.e., concern about, or actual changes in, food availability) has been associated with binge eating and binge eating disorder (BED), bulimia nervosa (BN), as well as general ED pathology and symptomatology (Becker et al, 2017 ; Hazzard et al, 2020 ; Lydecker & Grilo, 2019 ; Rasmusson et al, 2019 ; Zickgraf et al, 2022 ). Food insecurity may be exacerbated during COVID‐19 due to increased financial stress and economic limitations, as well as the “panic buying” behaviors and shortage of staple foods that characterized the initial phases of the pandemic (Khosravi, 2020 ; Weissman et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Food insecurity compromises health because of its association with poor diet quality, obesity, depression, and high mortality rates [30]. It increases the risk of eating disorders, depression, and anxiety 1.19 times [31]. Maternal depression increases the risk of delayed early childhood development when associated with household food insecurity [32].…”
Section: Discussionmentioning
confidence: 99%
“…A recent national study ( Oh et al, 2022 ) found that around 12% of students disclosed suicidal ideation (SI), suggesting that college students might be at greater suicide risk compared with the general population (10.8% [Dubé et al, 2021] ). The COVID-19 pandemic has caused public health, social, and economic turmoil that exacerbated challenges for millions of college students ( DeVylder et al, 2021 ; Oh, Marinovich, Jay, et al, 2021 ; Oh, Marinovich, Rajkumar, et al, 2021 ; Zickgraf et al, 2022 ). Uncertainty and concerns over one's health and safety, education, and employment during the pandemic might have posed a threat to collegiate mental health, placing students at higher risk for mental health problems and suicide ( Cao et al, 2020 ; King et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some students had concerns and fear of being infected or infecting others, and some worried about or experienced the loss of social ties due to lockdown/shelter-in-place and school closures for in-person learning, which exacerbated social isolation and loneliness ( Tei and Fujino, 2022 ). During the early pandemic, some college students struggled with food security and financial hardship due to the loss of employment or financial assistance ( Peltz et al, 2020 ; Zickgraf et al, 2022 ). Students might also have difficulties sustaining their academic performance to complete their degrees because of psychological disturbance associated with social and economic turmoil ( Duffy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%